2018
DOI: 10.1007/s00268-018-4786-4
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Perioperative Care in Esophagectomy: Enhanced Recovery After Surgery (ERAS®) Society Recommendations

Abstract: Introduction Enhanced recovery after surgery (ERAS) programs provide a format for multidisciplinary care and has been shown to predictably improve short term outcomes associated with surgical procedures. Esophagectomy has historically been associated with significant levels of morbidity and mortality and as a result routine application and audit of ERAS guidelines specifically designed for esophageal resection has significant potential to improve outcomes associated with this complex procedure. Methods A team … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
376
1
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 458 publications
(395 citation statements)
references
References 321 publications
(298 reference statements)
6
376
1
12
Order By: Relevance
“…As complications were independently predictive of survival, regardless of tumour stage or grade, it follows that reducing the likelihood of complications may improve survival. Recent studies have focused on prehabilitation, enhanced recovery after surgery, intensive postoperative physiotherapy and incentive spirometry, with mixed findings. Additionally, minimally invasive and hybrid oesophagectomy techniques appear to reduce pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…As complications were independently predictive of survival, regardless of tumour stage or grade, it follows that reducing the likelihood of complications may improve survival. Recent studies have focused on prehabilitation, enhanced recovery after surgery, intensive postoperative physiotherapy and incentive spirometry, with mixed findings. Additionally, minimally invasive and hybrid oesophagectomy techniques appear to reduce pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…Intake of carbohydrates up to 2 h before anaesthesia does not increase rates of delayed gastric emptying and is recommended prior to surgery [44]. Other practices [6,34] in ERAS protocols include the use of preoperative carbohydrates, procedures to avoid hypothermia, complete avoidance of the use of nasogastric tubes, and early oral feeding and mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were included in the meta-analysis when they adhered to consensus guidelines for ERAS protocols [6,34]. The basic characteristics of the included studies are shown in Table 1.…”
Section: Study and Eras Characteristicsmentioning
confidence: 99%
“…QoL; quality of life as measured by the EORTC C30 and OG-25 questionnaires QoR; quality of recovery as measured by the QoR-40 questionnaire. which state that regional analgesia should be the backbone of pain management in enhanced recovery after esophagectomy protocols [25]. In absence of trials in patients undergoing MIE, both epidural and paravertebral analgesia were considered to be suitable options based on extrapolated evidence, although no recommendations in favour of either modality could be made [25].…”
Section: Discussionmentioning
confidence: 99%
“…which state that regional analgesia should be the backbone of pain management in enhanced recovery after esophagectomy protocols [25]. In absence of trials in patients undergoing MIE, both epidural and paravertebral analgesia were considered to be suitable options based on extrapolated evidence, although no recommendations in favour of either modality could be made [25]. Retrospective cases series suggest that paravertebral analgesia is associated with less technical failure and reduces the incidence of hypotensive events, which may promote postoperative recovery [26,27].…”
Section: Discussionmentioning
confidence: 99%